Report of the Working Group on Adolescents for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, Government of India, 2001)
The Report of the Working Group on Adolescents for the Tenth Five-Year Plan (2002–2007), prepared under the aegis of the Planning Commission, presents a comprehensive analysis of the demographic, social, educational, psychological, and health-related challenges confronting India’s adolescent population, defined as individuals aged 10–19 years and constituting nearly 23 percent of the national population. Recognizing adolescence as a critical transitional phase marked by rapid physical growth, emotional maturation, identity formation, and increasing socio-economic responsibility, the report underscores the urgent need for focused investment in this age group to harness their potential for nation-building and social transformation. The situational analysis highlights significant concerns including adverse sex ratios reflecting deep-rooted gender discrimination, persistent though narrowing gender gaps in literacy, high dropout rates particularly at middle and secondary levels, rural–urban and inter-state disparities in educational access, and limited opportunities for skill development and career guidance. It further draws attention to psychological stress arising from academic pressure, changing social values, inadequate communication within families, and lack of counselling services, alongside rising incidences of juvenile delinquency, substance abuse, high-risk sexual behaviour, and inadequate awareness regarding reproductive health and HIV/AIDS. The report emphasizes that adolescents, though often perceived as problematic, possess strong idealism and a desire for participation, which, when nurtured through supportive environments, education reforms, life skills training, health services, gender-sensitive interventions, and participatory development programmes, can transform them into productive and responsible citizens. By advocating a holistic, multi-sectoral approach encompassing education, health and nutrition, counselling, employment orientation, media engagement, research, and effective governance mechanisms, the Working Group envisions a coordinated strategy to empower adolescents, address vulnerabilities, and integrate their development into the broader socio-economic objectives of the Tenth Plan period.
Government of India Planning Commission June - 2001
Keywords: Adolescent Development; Tenth Five-Year Plan; Situational Analysis; Gender Disparity; Sex Ratio; Educational Attainment; School Dropout Rates; Psychological Concerns; Juvenile Delinquency; Substance Abuse; Career Guidance; Health And Nutrition